Kognitive Neurophysiologie des Menschen - Human cognitive neurophysiology Vol. 3 (2010) - (:unkn) unknown; Justus Liebig University Giessen (My University, 2010)
P. Etevenon: Meditation as a state of consciousness: A personal account. K. Suzuki & H. Shinoda: Error-related components and impulsivity related to speedand to accuracy trade-off. W. Skrandies: Abstracts of the 18th German EEG/EP Mapping Meeting.
Keywords: ddc:610